2015
DOI: 10.1111/cas.12618
|View full text |Cite
|
Sign up to set email alerts
|

Human T‐cell leukemia virus type 1 Tax oncoprotein represses the expression of the BCL11B tumor suppressor in T‐cells

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) is the etiological agent of adult T cell leukemia (ATL), which is an aggressive form of T-cell malignancy. HTLV-1 oncoproteins, Tax and HBZ, play crucial roles in the immortalization of T-cells and/or leukemogenesis by dysregulating the cellular functions in the host. Recent studies show that HTLV-1-infected T-cells have reduced expression of the BCL11B tumor suppressor protein. In the present study, we explored whether Tax and/or HBZ play a role in downregulating BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…6 A). Like the regulatory proteins Tat of HIV and Tax of HTLV [ 65 , 66 ], which transactivate viral transcription (for review, [ 67 , 68 ]), P50 also acted as a regulatory protein. Indeed, P50 transrepressed the viral transcription and consequently decreased the FL RNA translation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6 A). Like the regulatory proteins Tat of HIV and Tax of HTLV [ 65 , 66 ], which transactivate viral transcription (for review, [ 67 , 68 ]), P50 also acted as a regulatory protein. Indeed, P50 transrepressed the viral transcription and consequently decreased the FL RNA translation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…BCL11B is implicated in multiple biological processes, including cell proliferation ( 51 ), apoptosis ( 52 ) and the immune response ( 53 ), as well as different pathological conditions, including cancer ( 54 ), inflammation ( 55 ), cardiac hypertrophy ( 56 ) and human immunodeficiency virus latency ( 57 ). Previous studies have demonstrated that BCL11B also contributes to T-cell development and T-cell identity ( 53 , 58 , 59 ). Additionally, BCL11B serves a critical role in the production and release of cytokines, including IFN-γ, IL-5 and IL-13 ( 60 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Almost 5% of HTLV‐1‐positive individuals develop adult T cell leukemia/lymphoma (ATL), though the process of disease occurrence remains poorly understood . The virus encodes two proteins that have been reported to result in oncogenesis: Tax and HTLV‐1 basic leucine zipper factor (HBZ) …”
Section: Oncogenic Viruses and Their Role In Causing Aneuploidymentioning
confidence: 99%